Un impressor francès i un cirurgià mallorquí a la València del segle XVII. - MUÑOZ BENAVENT, MARIA; DE PASCALIS, GIORGIA (Scripta)
The printer Laurent Durand, active in Lyon during the 16th century, stablished important commercial relations with Spain during his career. He published many Spanish authors, all Jesuit religiousmen. He developed a close relationship with Valencia, where he lived, at least, in 1614. In 1633 the Mallorcan master surgeon Antoni Roig wrote a treatise on surgery in Catalan. This text was intended to be used to prepare for the master surgeon exams in the city of Palma. With this text we find a very unusual Latin exordium: it is full of verses from great ancient poets, but they are quoted in a careless way, as if quoting them from memory. After much study we discovered that the verses were copied from a dedication written by Durand to the college of medicine of Valencia. The exordium, then, opens more questions than it answers: who was Antoni Roig really? Where was he trained? What are his sources? Which is the origin of Laurent Durand's relationship with Valencia? How does this city connect a French printer with a Mallorcan master surgeon? This article aims to delve deeper into the nature of these characters and their relationship with the city of Valencia.